Sociodemographic profile of women who had homebirth in the municipality of Rio de Janeiro, from 2010 to 2017 (Research, Society and Development, 2022)
Home delivery is understood as the care provided to the woman during pregnancy, childbirth and the immediate puerperium in the home environment, performed by a qualified professional, freely chosen by the woman and registered in her Class Council. The objective of the study was to describe the sociodemographic profile of women in home births in the municipality of Rio de Janeiro, Brazil, from 2010 to 2017. Material and Method: This is a descriptive study, with a documental approach and a quantitative analysis, where assisted births were investigated and reported from January 2010 to December 2017, in the city of Rio de Janeiro. Data were collected from data from the Information System of the Unified Health System (DATASUS)/TABNET of the Municipal Health Secretariat of Rio de Janeiro from the Information System for Live Births (SINASC) on births in households between January 2010 and December 2017 and performed crosses of the variables for study analysis. The study showed that there was an increase in the number of home births and that these occurred mostly in middle-upper-class neighborhoods, young, white, single, full-term and single-fetus.